ADJUSTMENT AND BEHAVIOR PROBLEMS IN CHILDREN - Kahveci, Müedin; Saban, Yasemin (International Scientific Journal Vision, 2023)
Adaptation is adjusting according to the environmental conditions in which the individual lives. Behavior is an individual’s observable actions. During the developmental period, children acquire different skills. He may need some help with acquiring these new skills. The issues faced by children in developmental stages are diverse. If children encounter obstacles in solving issues during their developmental period, the solution to these problems, considered normal, is postponed to the following developmental periods and later ages. The issues that arise in this situation are called adjustment and behavioral disorders. This study aims to examine adjustment and behavior problems in children.